Everyday emotional experience of adults with attention deficit hyperactivity disorder: evidence for reactive and endogenous emotional lability. Issue 16 (15th May 2014) - Skirrow, C.; Ebner-Priemer, U.; Reinhard, I.; Malliaris, Y.; Kuntsi, J.; Asherson, P.
Abstract : Background: Emotional lability (EL), characterized by negative emotional traits and emotional instability, is frequently reported in children and adults with attention deficit hyperactivity disorder (ADHD). However, EL is primarily assessed using retrospective self-report, which is subject to reporting bias and does not consider the potential influence of positive and negative everyday experiences. Method: Ambulatory assessment was carried out in 41 men with ADHD without co-morbidity, current medication or substance abuse, and 47 healthy control participants. Reports of negative and positive emotions (irritability, frustration, anger, happiness, excitement) and the occurrence of bad and good events were completed eight times daily during a working week. Group differences in emotional intensity and instability were investigated using multilevel models, and explored in relation to bad and good events and the Affective Lability Scale – Short Form (ALS-SF), an EL questionnaire. Results: The ADHD group reported significantly more frequent bad events, heightened intensity and instability of irritability and frustration, and greater intensity of anger. The results for positive emotions were equivocal or negative. Bad events significantly contributed to the intensity and instability of negative emotions, and showed a stronger influence in the ADHD group. However, covariation for their effect did not eliminate group differences. Small-to-moderate correlations were seen between intensity and instability of negative emotions and the ALS-SF. Conclusions: Adults with ADHD report heightened intensity and instability of negative emotions in daily life. The results suggest two components of EL in ADHD: a reactive component responsive to bad events and an endogenous component, independent of negative everyday events.